Early removal of drains and lines after liver transplantation to reduce the length of hospital stay and enhance recovery – A systematic review of the literature and expert panel recommendations. Issue 10 (9th December 2022) - Goldaracena, Nicolas; Bhangui, Prashant; Yoon, Young‐In; Vargas, Paola A.; Spiro, Michael; Raptis, Dimitri Aristotle; Tokat, Yaman; ,
Abstract: Background: The timing of removing abdominal drains, central venous catheters (CVC), and urinary catheters (UC) on post liver transplantation (LT) outcomes is not well elucidated. Objectives: To provide international expert panel recommendations and guidelines on time of drain and catheter removal as a part of an ERAS protocol to reduce the length of hospital stay and enhance recovery. Methods: Systematic review following PRISMA guidelines and recommendations using the GRADE approach derived from an international expert panel. Papers considered were those reporting one or more outcomes of interest related to drainage and line removal in the setting of LT. POSPERO Protocol ID: CRD42021238349 Results: On analyzing five relevant studies pertaining to drains in patients undergoing LT (four retrospectives and one prospective), the length of hospital and/or ICU stay was similar or shorter, and postoperative morbidity and mortality were lower in those without drains. No studies pertaining specifically to the time of removal of drains, CVC's, or UC's in LT were found. Studies in patients undergoing major abdominal surgery or hepatectomies recommend early removal of CVC and UC to reduce catheter‐associated infections. Conclusions: Based more on expert recommendation, we propose that abdominal drains, if placed during LT, should be removed by postoperative day 5 after LT, based on quantity and fluid characteristics ( Quality of Evidence ; Low to Moderate | Grade of Recommendation; Strong). Larger studies are needed to more reliably determine indications for early drain and line removal in an ERAS protocol setting.